A New Proposed Model on Industrial Researchers ' Information Behaviour Based on Wilson ' s Models - Makinde, Olayinka Babayemi; Jiyane, Glenrose Velile; Mugwisi, Tinashe (University of Dar es Salaam Library Journal, 2021)
The recognition of a major behaviour is very important for the design and organization of a system that provides information for a particular category of researchers. The purpose of this study is to propose a new model of industrial researchers ' information behaviour in order to motivate the creation of well-structured systems for the provision of adequate research information to this category of researchers. The new model is based on the integration of Wilson ' s models (1981, 1996 and 1999) of information behaviour and results from a larger doctoral project on industrial researchers ' information behaviour. Both quantitative and qualitative research approaches were used. Survey questionnaires were distributed to industrial researchers and interviews were conducted for librarians of a federal industrial research institute in Nigeria. The new model must be understood within the context of the particular characteristics of the geographical area and institution in which the fieldwork was carried out €“ especially with the result that showed that mobile phones/iPads connected to the Internet were a more helpful information source than the institute ' s library. In order to assess the extent to which this new model applies to industrial researchers in other settings, similar projects employing the same methods would be of immense consequence.